Savings-Investment Gap in Sub Saharan Africa: Does the Interaction of Financial Sector Development and Migrant Remittances Matter? (2022)
This study analyzes the interactive effects of migrant remittances and financial development on savings-investment gap for a panel of 18 Sub-Saharan Africa (SSA) countries from 1990-2017. Results from a panel ARDL model show that migrant remittances reduce savings-investment gap in the long run. The gap is further reduced when the individual effect of financial development, and the interactive effects of migrant remittances and financial development are taken into consideration. Further analysis reveals evidence of widening effects of rising real GDP growth and bank deposits over a long-term horizon, while higher private sector credit widened the savings-investment gap only in the short-run. The study suggests the need for a policy to reduce migrant remittance transfer costs and encourage beneficiaries to prioritize investment over consumption.